2013
DOI: 10.3390/ijms140715105
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae Infection in Atherosclerotic Lesion Development through Oxidative Stress: A Brief Overview

Abstract: Chlamydia pneumoniae, an obligate intracellular pathogen, is known as a leading cause of respiratory tract infections and, in the last two decades, has been widely associated with atherosclerosis by seroepidemiological studies, and direct detection of the microorganism within atheroma. C. pneumoniae is presumed to play a role in atherosclerosis for its ability to disseminate via peripheral blood mononuclear cells, to replicate and persist within vascular cells, and for its pro-inflammatory and angiogenic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 101 publications
0
49
0
6
Order By: Relevance
“…In atherosclerosis, the involvement of e. pneumoniae, a respiratory pathogen, has been supported by seroepidemiology, identification of the microorganism within atheroma by immunochemistry and electron microscopy, and direct detection of chlamydial DNA within atheroma by polymerase chain reaction (PCR) (13)(14)(15). Several in vivo studies have shown that e. pneumoniae contributes to exacerbation of lesions in hyperlipidaemic animal models, suggesting thatthis microorganism is aco-risk factor with hyperlipidaemia (15).…”
Section: The Involvement Ofc Pneumoniae In Cardiovascular Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…In atherosclerosis, the involvement of e. pneumoniae, a respiratory pathogen, has been supported by seroepidemiology, identification of the microorganism within atheroma by immunochemistry and electron microscopy, and direct detection of chlamydial DNA within atheroma by polymerase chain reaction (PCR) (13)(14)(15). Several in vivo studies have shown that e. pneumoniae contributes to exacerbation of lesions in hyperlipidaemic animal models, suggesting thatthis microorganism is aco-risk factor with hyperlipidaemia (15).…”
Section: The Involvement Ofc Pneumoniae In Cardiovascular Diseasementioning
confidence: 99%
“…Several in vivo studies have shown that e. pneumoniae contributes to exacerbation of lesions in hyperlipidaemic animal models, suggesting thatthis microorganism is aco-risk factor with hyperlipidaemia (15). In addition, in vitro studies have demonstrated that this microorganism is able to disseminate systematically from the lungs through infected peripheral blood mononuclear cells (PBMC) and to localize in multiple tissues, including the arterial wall (16,17).…”
Section: The Involvement Ofc Pneumoniae In Cardiovascular Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…C. pneumoniae was also found to elicit inflammatory cytokines, inducing chronic inflammation [15]. Furthermore, C. pneumoniae has been shown to induce foam cell formation, smooth muscle cell multiplication, platelet aggregation, and production of reactive oxygen intermediates and cellular adhesion molecules [15,16]. Paradoxically, other in vivo and in vitro studies have failed to link C. pneumoniae with atherosclerosis [17] and, therefore, it remains controversial whether C. pneumoniae could actively play a role in vascular disease development or is an innocent bystander.…”
Section: Introductionmentioning
confidence: 99%